Encyclopedia of New Jersey - Lurie, Maxine N., 1940-; Mappen, Marc (Rutgers University Press, 2004)
Contains nearly original articles, along with illustrations and maps, collecting a wealth of information about the state of New Jersey.
Keywords: New Jersey -- Encyclopedias.; New Jersey -- Encyclopédies.; HISTORY -- State & Local.; HISTORY -- State & Local -- General.; New Jersey; Electronic books.; Encyclopedia; encyclopedias.; Encyclopedias; Encyclopedias.; Encyclopédies.